Using Data on Bike-Sharing System User Stopovers in Smart Tourism: A Case Study - Krystian Banet (Communications - Scientific letters of the University of Zilina, 2021)
Bike-sharing systems are an important element in development of the smart cities and datasets from these systems are one of the ways to obtain large amount of information on bicycle traffic. These usually contain data on the origin and destination of each trip, as well as its time and duration. Alongside the basic data, some operators also provide information on the exact route picked by each user. This allows researchers to study stopovers, which may serve as a source of interesting information on human behaviour in public spaces and, as a consequence, help improve its analysis and design. However, using the raw data may lead to important errors because most stops occur in the vicinity of bike stations or are related to traffic problems, as evidenced by the case study of Cracow. The data filtering method proposed below opens up the possibility for using such datasets for further research on bike user behaviour and public spaces.